FORMULATION AND EVALUATION OF MUCOADHESIVE BUCCAL TABLET OF SIMVASTATIN - A. M. PETHE; S. P. SALUNKHE (International Journal of Pharma and Bio Sciences, 2014)
In present study mucoadhesive buccal tablet of simvastatin was prepared. Solubility of Simvastatin was enhanced by complexing Simvastatin with β-CD in 1:2 molar concentrations. Six different formulations of tablets of Simvastatin containing the polymers in various combinations were prepared by direct compression method and characterized for swelling studies, % matrix erosion, surface pH, mucoadhesive properties, in-vitro release studies. All the formulations showed the satisfactory results bioadhesive performance, surface pH ,physical& mechanical properties . The swelling index was proportional to carbopol content & other bio-adhesive polymer. The surface pH of all tablets was found to be satisfactory, close to neutral pH; hence, buccal cavity irritation should not occur with these tablets. Drug release and drug diffusion from the tablets were depended on the ratio and type of the polymer used in the formulation. Tablets containing Carbopol and HPMC K100 in the ratio of 4:1 had the maximum percentage of in-vitro drug release for 7h. The formulation F4was optimized based on good bioadhesive strength (45 ± 0.55 g) and sustained in vitro drug release (65.96 % for 7h). The chosen tablet containing 10 mg of simvastatin performed 7h sustained drug release with desired therapeutic concentration.